Nobres quintais : abordagem etnoecológica dos recursos vegetais cultivados nos quintais urbanos de Nobres – Mato Grosso, Brasil - Campos, Pedro Araujo (2012)
The gardens are one of the oldest forms of management and domestication of plants and animals, are systems that essentially consist of a combination of trees, shrubs, herbaceous, sometimes associated with small domestic animals. This work is part on Project: Flora, Vegetação e Etnobotânica em Nobres, developed with funding from FAPEMAT and seeks to analyze specifically the urban and peri-urban gardens and the relationship between their supporters with floristic elements. For this study the objective was to analyze the relationships and importance of plant resources found in Nobres homegardens and highlight the role of these areas for conservation of biological and cultural diversity. To do the survey of home grown plant species, we visited 33 homegardens distributed in 16 neighborhoods in the city of Nobres. The ethnobotanical data collection was given through intentional nonprobabilistic samples selecting people known for been holders of knowledge about the use and cultivation of plants – elders, traditional healers, faith healers, root collectors and midwives, starting from a key informant who introduced the next informant and facilitated our entry into people's homes. The identification of the plants occurred with the help of guides and identification keys from photographic records and lists of plants obtained in guided tours in backyards, with the classification adopted following APG III. We avoided the collection of material for herborization, the collection of material for herborization was avoided since there are usually few individuals of any species in each yard, besides mostly of these plants are common and cosmopolitan. Most of the green area of the city of Nobres - MT is located in homegardens. For the population of Nobres the garden is usually the portion of land adjacent to the residence where they grow plant species considered to be useful – as shade, food, medicine, or the inherent beauty and delight of being close to plants. We identified 220 plant species from 80 botanical families. Based on the usage quoted by the informants, the species were categorized into food, ornamental, medicinal, mystical, shading and minor uses, a plant may belong to more than one category of use. We calculated the importance value of plants cultivated by the urban population of Nobres by the index “Concordância quanto o Uso Principal / Agreement on the Main Usage” (CUP), based on knowledge the people known to be experts in the use and cultivation of plants by the identified with the help of the population. The most common species were: banana (Musa x paradisiaca L.) e coconut (Cocos nucifera L.) present in 81,81% of studied gardens; lemon (Citrus limon (L.) Osbeck) in 72,72%; mango (Mangifera indica L.), papaya (Carica papaya L.) and guava (Psidium guajava L.) in 66,66%. As for the use, most plants falls in ethnocategory of use as medicinal and food, stressing the importance that the gardens play in food security and health of families. The presence of introduced species from other regions among the most used reflects the history of colonization of the region of Nobres in a broad historical spectrum, with cultural influences of: indigenous, black slaves and the Portuguese and recently from the arrival of Southern Brazilian people. Many gardens shelter a collection of species that reflect Nobres regionalism, such as bocaiúva (Acrocomia aculeata (Jacq.) Lodd. ex Mart.), the fruta-banana (Ecclinusa ramiflora Mart.), sigá (Hyptis ovalifolia Benth.) and rabo-de-caxinganga (Phlebodium decumanum (Willd.) J. Sm.). These spaces play an important role in the conservation of biological and cultural diversity of the regionThis fact must be taken into account when developing public policies and conservation strategies, including the general population which holds an important knowledge of local dynamics and integral part of the ecosystem.